The A to Z of the Orthodox Church - Prokurat, Michael, 1950-; Prokurat, Michael, 1950- .; Golitzin, Alexander; Peterson, Michael D., 1945- (Lanham : Scarecrow Press, 2010)
Of the three major branches of Christianity, Orthodoxy is the least known and most misunderstood. The A to Z of the Orthodox Church provides students, researchers, and specialists with a desk encyclopedia of the theology and theologians, saints, sinners, places and events of the Eastern Church. Two millennia of the religion are surveyed in over five hundred concise entries, concentrating primarily on the last 150 years.
Originally published in 1996 as Historical dictionary of the Orthodox Church.
Includes bibliographical references (p. 349-437).
Description based on print version record.
Keywords: Orthodox Eastern Church -- History -- Dictionaries; Orthodox Eastern Church -- Dictionaries; RELIGION / Christianity / Orthodox; Electronic books